Impact of mobile fitness apps on exercise adherence among Filipino youth - Batiquin, Mariane (Edelweiss Applied Science and Technology, 2025)
Physical inactivity among Filipino adolescents has reached alarming levels, with only 15.4% meeting the recommended physical activity guidelines. Mobile fitness applications have emerged as potential interventions to address this public health concern. This study investigated the impact of mobile fitness apps on exercise adherence among Filipino senior high school students, examining behavioral changes, motivation factors, and long-term engagement patterns. A quantitative research design was employed with Filipino senior high school students aged 16-18 years. Participants used mobile fitness applications over a 10-week period, with measurements of exercise adherence, physical activity levels, and motivational factors assessed at baseline and post-intervention. The findings revealed significant improvements in exercise adherence among Filipino youth who utilized mobile fitness applications. Participants demonstrated increased physical activity levels, enhanced intrinsic motivation, and sustained engagement with fitness routines. Gamification elements, social features, and progress tracking emerged as key factors contributing to improved adherence. Mobile fitness apps present a viable and effective intervention strategy for improving exercise adherence among Filipino adolescents. The integration of behavioral psychology principles, particularly Self-Determination Theory and gamification elements, effectively addresses the motivational challenges associated with sustained physical activity. These findings have important implications for public health initiatives targeting youth physical inactivity in the Philippines and similar contexts.